Implementasi Program Matrikulasi Dalam Meningkatkan Penyataraan Keilmuan Keislaman di Pondok Pesantren Al-Ittifaqiah Indralaya - Murtosiah, Siti; Ichromsyah Arrochman (TAUJIH: Jurnal Pendidikan Islam, 2025)
Deep and relevant Islamic knowledge is essential for shaping strong and applicable understanding among new students. The matriculation program serves as an effort to enhance basic knowledge and equalize Islamic scientific competencies among new students, who often come from diverse educational backgrounds. This study aims to develop a comprehensive understanding of the planning. Implementation, and evaluation of the matriculation program in improving the equalization of Islamic knowledge at Pondk Pesantren Al-Ittifaqiah Indralaya. This research employs a qualitative approach using the grounded theory method, which focuses on deriving theory from systematically collected data trough in depth interviews, participant observation, and documentation. The findings indicate that the planning process is carried out participatively trough a needs assessment approach; the implementation of the program is adaptive and based on the varying competency levels of the students, and the evaluation is conducted hostically, covering cognitive, affective, and character development aspects. Throught the stages of open cding, axial coding, and selective coding. This study successfully formulates a substantive theory regarding the dynamics of organizing the matriculation program within the pesantren envirotment. Theoretically, the study contributes to understanding matriculation as a strategic effort to equalize students’ competencies and broadens insight into the diversity of students’ educational bacgrounds, thereby emphasizing the importance of differentiation and inclusivity in pesantren learning. Practically, concrete illustration of how a well designed matriculation program can address initial competency gaps among students, enhance the effectiveveness of regular learning, and serve as a reference for developing more responsive policies, curricula, and instructional methods aligned.